PERAN LINGKUNGAN DALAM MENINGKATAN MUTU PENDIDIKAN - Elvi Syoviana; Afrizen Afrizen; Rusdinal Rusdinal; Nurhizrah Gustituati; Nidya Fitri (Jurnal Dedikasi Pendidikan, 2021)
The environment has a strategic role in the world of education, especially in the learning process. With the environment, human beings and especially learners understand and understand about education itself. Innovation continues to be developed along with the times. With this environment will change the thinking patterns and behavior of students. The purpose of this research is to find out how the role of the environment in improving the quality of education. The method used is qualitative, descriptive approach. The results found that the environment plays a very important role in improving educators.